2013
DOI: 10.1002/pros.22678
|View full text |Cite
|
Sign up to set email alerts
|

Function of mutant and wild‐type plexinB1 in prostate cancer cells

Abstract: BACKGROUNDSemaphorins act as chemotactic cues for cell movement via their transmembrane receptors, plexins. Somatic missense mutations in the plexinB1 gene coupled with overexpression of the protein frequently occur in prostate tumors, indicating a role for plexinB1 in the pathogenesis of prostate cancer. However, the effect of semaphorin/plexin signaling is highly context dependent and whether plexinB1 acts as an inducer or inhibitor of prostate tumor progression in this context is not known.METHODSThe respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…LNCaP-LN3, a derivative of the prostate cancer cell line LNCaP, has lost the mutant allele of plexin-B1 found in LNCaP, and it expresses wild-type (WT) plexin-B1 only. 23 LNCaP and LNCaP-LN3 cells were serum starved and then treated with Sema4D (2 μg/ml) for 48hrs or with PBS or dihydrotestosterone (DHT, 1 nM) as controls. Expression of KLK3 increased significantly in both cell lines following treatment with Sema4D ( Figure 1a).…”
Section: Sema4d Affects the Expression Of Androgen-responsive Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…LNCaP-LN3, a derivative of the prostate cancer cell line LNCaP, has lost the mutant allele of plexin-B1 found in LNCaP, and it expresses wild-type (WT) plexin-B1 only. 23 LNCaP and LNCaP-LN3 cells were serum starved and then treated with Sema4D (2 μg/ml) for 48hrs or with PBS or dihydrotestosterone (DHT, 1 nM) as controls. Expression of KLK3 increased significantly in both cell lines following treatment with Sema4D ( Figure 1a).…”
Section: Sema4d Affects the Expression Of Androgen-responsive Genesmentioning
confidence: 99%
“…Furthermore, knockdown of ErbB2 expression inhibits the Sema4D-induced motility of LNCaP cells, suggesting that activation of the Sema4D/plexin-B1 signalling pathway involving ErbB2 promotes the invasive behaviour of prostate cancer cells. 23 ErbB2 overexpression occurs in late-stage prostate cancer, as do mutations in plexin-B1. Sema4D/plexin-B1 signalling may therefore increase the invasive characteristics of prostate cancer cells via activation of ErbB2 and Rho and via mutation of plexin-B1 in late-stage prostate cancer, in a similar way to breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…232 Regardless of the mechanisms involved, there are numerous observations suggesting that sema4D plays a stimulatory role in the progression of several types of tumors including head and neck tumors, breast carcinomas, ovarian cancinomas, pancreatic carcinoma, prostate cancer and soft tissue sarcomas such as osteosarcoma. [233][234][235][236][237][238][239] These observations lead to the development of inhibitory humanized antibodies that are developed as anti-tumorigenic drugs that target sema4D. 240 However, there are also opposite observations.…”
mentioning
confidence: 99%
“…36 Similar observations were also reported in prostate cancer cells. 238 It was recently also observed that the activation of plexin-B1 by Sema4D in breast carcinoma cells results in tyrosine phosphorylation of plexin-B1 by Met, thus creating a docking site for the SH2 domain of growth factor receptor bound-2 (Grb2). Grb2 is thereby recruited into the plexin-B1 receptor complex and through its SH3 domain, interacts with p190 RhoGAP and mediates RhoA deactivation and leads to the subsequent inhibition of breast carcinoma cells motility.…”
mentioning
confidence: 99%
“…Damola et al (2013) reported that the invasive phenotype of prostate cancer cells could be increased by Plexin B1 signals via ErbB2. Plexin B1-mediated signalling pathways can be blocked by Plexin B1 mutations, which inhibit cell motility.…”
Section: Discussionmentioning
confidence: 98%